Synergistic Effect of Simple Sugars and Carboxymethyl Cellulose on the Production of a Cellulolytic Cocktail from Bacillus sp. AR03 and Enzyme Activity Characterization - Manfredi, Adriana Paola (2016)
A cellulase-producing bacterium isolated from pulp and paper feedstock, Bacillus sp. AR03, was evaluated by means of a factorial design showing that peptone and carbohydrates were the main variables affecting enzyme production. Simple sugars, individually and combined with carboxymethyl cellulose (CMC), were further examined for their influence on cellulase production by strain AR03. Most of the mono and disaccharides assayed presented a synergistic effect with CMC. As a result, a peptone-based broth supplemented with 10 g/L sucrose and 10 g/L CMC maximized enzyme production after 96 h of cultivation. This medium was used to produce endoglucanases in a 1-L stirred tank reactor in batch mode at 30 °C, which reduced the fermentation period to 48 h and reaching 3.12 ± 0.02 IU/mL of enzyme activity. Bacillus sp. AR03 endoglucanases showed an optimum temperature of 60 °C and a pH of 6.0 with a wide range of pH stability. Furthermore, presence of 10 mM Mn2+ and 5 mM Co2+ produced an increase of enzyme activity (246.7 and 183.7 %, respectively), and remarkable tolerance to NaCl, Tween 80, and EDTA was also observed. According to our results, the properties of the cellulolytic cocktail from Bacillus sp. AR03 offer promising features in view of potential biorefinery applications.